Novel β-N-acetylglucosaminidases from Vibrio harveyi 650: Cloning, expression, enzymatic properties, and subsite identification - Suginta, Wipa (BioMed Central, 2010)
BACKGROUND: Since chitin is a highly abundant natural biopolymer, many attempts have been made to convert this insoluble polysaccharide into commercially valuable products using chitinases and β-N-acetylglucosaminidases (GlcNAcases). We have previously reported the structure and function of chitinase A from Vibrio harveyi 650. This study t reports the identification of two GlcNAcases from the same organism and their detailed functional characterization. RESULTS: The genes encoding two new members of family-20 GlcNAcases were isolated from the genome of V. harveyi 650, cloned and expressed at a high level in E. coli. VhNag1 has a molecular mass of 89 kDa and an optimum pH of 7.5, whereas VhNag2 has a molecular mass of 73 kDa and an optimum pH of 7.0. The recombinant GlcNAcases were found to hydrolyze all the natural substrates, VhNag2 being ten-fold more active than VhNag1. Product analysis by TLC and quantitative HPLC suggested that VhNag2 degraded chitooligosaccharides in a sequential manner, its highest activity being with chitotetraose. Kinetic modeling of the enzymic reaction revealed that binding at subsites (-2) and (+4) had unfavorable (positive) binding free energy changes and that the binding pocket of VhNag2 contains four GlcNAc binding subsites, designated (-1),(+1),(+2), and (+3). CONCLUSIONS: Two novel GlcNAcases were identified as exolytic enzymes that degraded chitin oligosaccharides, releasing GlcNAc as the end product. In living cells, these intracellular enzymes may work after endolytic chitinases to complete chitin degradation. The availability of the two GlcNAcases, together with the previously-reported chitinase A from the same organism, suggests that a systematic development of the chitin-degrading enzymes may provide a valuable tool in commercial chitin bioconversion.